Spotkanie teraźniejszości z przeszłością i przyszłością. Wartość solidarności międzypokoleniowej we współczesnym nauczaniu papieskim - Ochman, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article is an attempt to show the question of intergenerational transfer in the optics of papal teaching. The ageing of the population is a fact that is difficult to argue with. Today, the question is no longer “how to live to old age?”, but “how to survive old age?”. The consequence of the problem posed in this way is a twofold possibility: either treating old age as a burden or as an important resource. The second solution is definitely more appropriate, because it brings mutual benefits, i.e. elders feel taken care of and involved in the life of the family and society, while the young generation can benefit from their experience and wisdom. Relationality and exchange of gifts are inscribed in experiencing the social nature of human and are also the faith in God. Inclusion older and younger people in the common course of life is an element that creates identity, gives a sense of inclusiveness, gives rise to community and brings out responsibility.